2005
DOI: 10.1111/j.1365-2966.2005.08804.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of binary fractions in globular clusters

Abstract: We study the evolution of binary stars in globular clusters using a new Monte Carlo approach combining a population synthesis code (startrack) and a simple treatment of dynamical interactions in the dense cluster core using a new tool for computing three‐ and four‐body interactions (fewbody). We find that the combination of stellar evolution and dynamical interactions (binary–single and binary–binary) leads to a rapid depletion of the binary population in the cluster core. The maximum binary fraction today in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
253
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(262 citation statements)
references
References 62 publications
6
253
3
Order By: Relevance
“…Theoretical studies of the evolution of binary populations are unaffected by from this shortcoming but usually also use this simple observable for reasons of comparison with observational data (see for example Kroupa 1995a; Kroupa & Bouvier 2003;Ivanova et al 2005;Hurley et al 2007;Sollima 2008). If we also do this here, we obtain the result described by Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies of the evolution of binary populations are unaffected by from this shortcoming but usually also use this simple observable for reasons of comparison with observational data (see for example Kroupa 1995a; Kroupa & Bouvier 2003;Ivanova et al 2005;Hurley et al 2007;Sollima 2008). If we also do this here, we obtain the result described by Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A flat binary period distribution has not only been observed in Sco OB II but also in other regions (e.g. Connelley et al 2008;Reipurth et al 2007) and has been used in several theoretical studies involving the evolution of primordial binary frequencies (Heggie & Aarseth 1992;Ivanova et al 2005;Hurley et al 2007). …”
Section: Methods and Cluster Setupmentioning
confidence: 99%
“…An initial binary fraction of a few percent is enough to postpone deep core collapse for many initial relaxation times (see Fregeau et al [2003] for discussion and references). In addition to playing a large part in the global evolution of a star cluster, dynamical interactions of binaries also strongly affect the formation and evolution of stellar and binary exotica, which include low-mass X-ray binaries, recycled pulsars, cataclysmic variables, and blue stragglers ( Hut et al 1991;Sigurdsson & Phinney 1995;Davies & Hansen 1998;Rasio et al 2000;Ivanova et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The binary evolution can also lead to their disruption (e.g., supernova explosions, star mergers, etc.). Furthermore, Ivanova et al (2005) have suggested that, to explain the currently observed low fraction of binary systems in cluster cores, the initial ratio of stars in binaries to all stars in GCs should be very high (even close to 100%). This means that the population of binary systems is much higher when a GC is formed, and that binaries may play an important role in the evolution of GCs.…”
Section: Discussionmentioning
confidence: 99%